2022
DOI: 10.1186/s12967-022-03477-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic DNA methylation of Zbtb7b regulates the population of double-positive CD4+CD8+ T cells in ulcerative colitis

Abstract: Background and aims Ulcerative colitis (UC) is a heterogeneous disorder with complex pathogenesis. Therefore, in the present study, we aimed to assess genome-wide DNA methylation changes associated explicitly with the pathogenesis of UC. Methods DNA methylation changes were identified by comparing UC tissues with healthy controls (HCs) from the GEO databases. The candidate genes were obtained and verified in clinical samples. Moreover, the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Moreover, DP CD4 + CD8 + T cells have functions of intestinal in ammation repression, IL-10 production, and bacterial invasion prevention 49 . We have previously discovered that the amount of DP CD4 + CD8 + T cells in colon tissues is substantially decreased compared the DSS-induced colitis with the health control 35 . Consequently, DP CD4 + CD8 + T cells could be an effective target for the treatment of colitis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, DP CD4 + CD8 + T cells have functions of intestinal in ammation repression, IL-10 production, and bacterial invasion prevention 49 . We have previously discovered that the amount of DP CD4 + CD8 + T cells in colon tissues is substantially decreased compared the DSS-induced colitis with the health control 35 . Consequently, DP CD4 + CD8 + T cells could be an effective target for the treatment of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, DP CD4 + CD8 + T cells can maintain a steady-state of the gut mucosa, and inhibit proin ammatory cytokine release during pathogenic infection 36 . Moreover, we previously demonstrated that the population of DP CD4 + CD8 + T cells was signi cantly decreased in UC mice colon samples 35 . Consequently, we investigated whether the oral administration of PELNs have an effect in the differentiation of DP CD4 + CD8 + T cells in mice colitis.…”
Section: Pelns Exert Therapeutic Effect Of Mice Colitis By Inducing T...mentioning
confidence: 91%
See 3 more Smart Citations